Valuation of Solar-Wind Power Plant Project and Impact on Stock Price - Panyagometh, Kamphol (International Journal of Energy Economics and Policy, 2018)
In Thailand, the Energy Policy and Planning Office, Ministry of Energy, has gradually developed a number of plans to promote renewable energy, such as the Alternative Energy Development Plan 2015–2036 (AEDP2015) and Power Development Plan 2010–2030 (PDP2010). This study examines valuation of power plant projects with two categories of renewable energy: solar power plants and wind power plants in Thailand. The valuation model shows the amount of electricity generated by solar energy and that generated by wind energy in each day and factors affecting electricity generation, such as cloud cover, temperature and wind speed. The amount of electricity generated is then used to calculate the Net Present Value (NPV), Interest Rate of Return (IRR), Payback Period (PB), and %Change of Stock Price when the project is announced, which can be used to support investors’ decision making process. Keywords: Renewable Energy; Valuation; Solar Power; Wind Power JEL Classifications: Q2; Q4; G11 DOI: https://doi.org/10.32479/ijeep.7075